2019
DOI: 10.1002/mdp2.53
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nonlinearity of acceleration histories to timber beam seismic response

Abstract: The single‐span timber frame has been subjected to near‐fault ground motion. The timber beam as a structural element has numerically been analyzed. The relationship between the acceleration histories of earthquake used in the numerical analysis with strain displacement has been discussed. For the analysis on acceleration histories of the earthquake, the specific part of acceleration histories of earthquake used in the numerical analysis has been zoomed in order to deeply analyze the effect of nonlinearity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…From the theoretical concept point of view, to provide an appropriate solution for this problem, and for solving and demonstrating this elasticity problem, the ABAQUS software has been employed. e ABAQUS has been employed to solve and explain many engineering problems in the various fields through numerical simulation [12,[14][15][16][17][18]. e ABAQUS has the ability to solve nonlinear problems in high quality.…”
Section: Problem Definitionmentioning
confidence: 99%
“…From the theoretical concept point of view, to provide an appropriate solution for this problem, and for solving and demonstrating this elasticity problem, the ABAQUS software has been employed. e ABAQUS has been employed to solve and explain many engineering problems in the various fields through numerical simulation [12,[14][15][16][17][18]. e ABAQUS has the ability to solve nonlinear problems in high quality.…”
Section: Problem Definitionmentioning
confidence: 99%
“…The mechanical properties, the strength and the bearing capacity of soils are very important in soil tension and compressive response during the soil is subjected to the loading in a different direction and it leads to developing displacement and deformation of the soil [6][7]. In other words, strain energy and damage have been investigated to solve several engineering problems and strain energy needs to be investigated further [8][9][10][11][12][13][14][15][16]. There are several types of research on flexural load applied on structure and materials [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There is a report on the improvement of the seismic resistance of historical industrial timber buildings [4]. Several research were reported on timber beam and column to study displacement, strain energy and seismic load sharing [5][6][7].…”
Section: Introductionmentioning
confidence: 99%